Pemanfaatan Media Visual Dalam Pembelajaran Insya - Putri, Najwaturraihanah Dafqa; Widianti, Ania (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses visual media as an Arabic language learning instrument that concentrates on writing skills, especially in insya (composing) learning. Some visual media that can be used in the learning process include: pictures or illustrations, short videos or animations, visual presentations, collages or inspiration boards, and field visits or virtual exploration. This research aims to analyze the use of visual media in insya' learning and its impact on students' writing abilities. Through the qualitative method of library research, namely a method of collecting data by understanding and studying theories from various literature related to the research. The results of the research show that the use of visual media in learning can provide benefits, including: (1) attracting students' interest and attention, (2) helping to concretize abstract ideas, (3) triggering students' creativity and imagination in develop writing.